Serum Ferritin in Helicobacter Pylori Infected Young Adult Female (Medical Forum Monthly, 2024)
Objective: To determine serum iron (Fe++), serum ferritin and total iron binding capacity (TIBC) in Helicobacter pylori (H. pylori) infected young adult female.Study Design: Case control studyPlace and Duration of Study: This study was conducted at the Department of Pathology, Indus Medical College Tando Muhammad Khan from September 2015- August 2016.Materials and Methods: A sample of 50 healthy controls and 50 H pylori positive female was studied. 5 ml of venous blood was collected after aseptic measures from ante cubital vein. 2 ml was shifted to EDTA mixed tubes for blood cell counts, and 3 ml was centrifuged at 3000 x rpm for ten minutes. Sera were separated to estimate serum iron profile. Helicobacter pylori stool specific antigen (HpSA) was detected by Elisa assay kit (Fortess). SPSS 22.0 (USA) was used for data analysis at 95% CI (P≤ 0.05).Results: The hemoglobin (Hb), hematocrit (Hct), RBC counts, serum Fe++, and serum ferritin were decreased with raised TIBC in H.pylori infected female (P<0.05). Serum ferritin in controls and cases (H.pylori +ve) was noted as 140.8 ± 20.09 and 126.5 ± 35.02 ng/dl respectively (P=0.014).Conclusion: The present study reports low serum iron, low serum ferritin and low hemoglobin and raised total iron binding capacity in Helicobacter pylori infected young adult female.